Comparison of Venture Capital Regulations in Indonesia and ASEAN Countries - Pasaribu, Simon Alex; Taufiq, Taufiq; Napitupulu, Diana Ria Winanti (Faculty of Law, Universitas Pattimura, 2025)
Introduction: By observing best practices from other ASEAN countries, Indonesia has a significant opportunity to reform its venture capital ecosystem to become more responsive, inclusive, and capable of supporting sustainable digital economic growth.Purposes of the Research: The purpose of this research is to identify the form and content of venture capital regulations currently enforced in Indonesia in comparison with other ASEAN countries, to analyze the similarities and differences in policies and regulatory approaches related to venture capital between Indonesia and ASEAN nations, and to determine the factors influencing the regulatory differences.Methods of the Research: A qualitative method was chosen because this approach enables the researcher to explore the policy context, legal structures, and socio-economic dynamics underlying venture capital regulations in each country.Findings of the Research: A more flexible, inclusive, and cross-sector collaborative regulatory approach will enhance Indonesia’s competitiveness in attracting investment and encouraging sustainable startup growth.